RETRACTED: Reasons for using parallel activation of logical rules in solving management tasks - Aladin Dmitry; Kotsenko Anton; Kim Radmir; Peresypkina Mariia; Varlamov Oleg (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001